2001
DOI: 10.1104/pp.125.1.339
|View full text |Cite
|
Sign up to set email alerts
|

Light Differentially Regulates Cell Division and the mRNA Abundance of Pea Nucleolin during De-Etiolation

Abstract: The abundance of plant nucleolin mRNA is regulated during de-etiolation by phytochrome. A close correlation between the mRNA abundance of nucleolin and mitosis has also been previously reported. These results raised the question of whether the effects of light on nucleolin mRNA expression were a consequence of light effects on mitosis. To test this we compared the kinetics of light-mediated increases in cell proliferation with that of light-mediated changes in the abundance of nucleolin mRNA using plumules of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
4
27
0
1
Order By: Relevance
“…Supporting this idea, alfalfa nucleolin is absent in stationary cells, but highly expressed before the onset of DNA replication at both the transcriptional and protein levels in logarithmically dividing cells (Bö gre et al, 1996). Furthermore, red light treatment induces pea nucleolin transcription 1 h prior to rRNA synthesis and coincides with increased cell division rates in pea apical internodes as well as increased nuclear number/ weight of pea plumules (Reichler et al, 2001). These data support a link between nucleolin and cell division in plants that may explain the growth defects and reduction in higher order venation characteristic of Arabidopsis parl1.…”
Section: Ribosomal Biogenesis and Parl1supporting
confidence: 54%
See 2 more Smart Citations
“…Supporting this idea, alfalfa nucleolin is absent in stationary cells, but highly expressed before the onset of DNA replication at both the transcriptional and protein levels in logarithmically dividing cells (Bö gre et al, 1996). Furthermore, red light treatment induces pea nucleolin transcription 1 h prior to rRNA synthesis and coincides with increased cell division rates in pea apical internodes as well as increased nuclear number/ weight of pea plumules (Reichler et al, 2001). These data support a link between nucleolin and cell division in plants that may explain the growth defects and reduction in higher order venation characteristic of Arabidopsis parl1.…”
Section: Ribosomal Biogenesis and Parl1supporting
confidence: 54%
“…All transformed yeast were grown at For liquid growth complementation experiments, three samples each of both Dnsr1 mutant haploid strains containing either pEGH alone or pEGH containing the full-length Arabidopsis PARL1 cDNA, as well as three samples of the wild-type haploid strain transformed with pEGH alone were transferred from noninducing plates and grown in 5 mL noninducing media overnight. As described by Reichler et al (2001), equal amounts of each culture were then transferred to another 5 mL of noninducing media and grown to early log phase. Equal amounts of these cultures were then transferred to inducing media and grown to saturation while growth rate was monitored hourly by OD 600 readings.…”
Section: Yeast Strains and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, the expression of nucleolin is restricted to proliferating tissues of the plant (Bo¨gre et al 1996). In peas, the expression of nucleolin is regulated by light, following a close correlation with the effects of light in increasing cell proliferation and mitotic activity (Reichler et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in morphogenesis by the effects of spectral green light showed that it is an important factor affecting plant development, contrary to some studies that reported green light to be innocuous to growth (Reichler et al, 2001). According to Folta and Maruhnich (2007), phytochromes and cryptochromes are responsible for the absorption of green light.…”
Section: Discussionmentioning
confidence: 59%